A Density Functional Theory Study of 4-OH Aldehydes - Huda Khanam; Ruchi Singh; Jyoti Pandey (Chemistry Proceedings)
According to certain theories, aldehydes play a significant role as precursor species in the creation of new atmospheric particles. In the current study, we first optimized the structure of the title compound by using the B3LYP 631-G (d, p) basic set. This compound’s electrostatic potential, electrophilicity (ω), chemical potential (µ), chemical hardness (η), and maximum quantity of electronic charge transfer (Nmax) have all been carefully examined. The hyperconjugated electron interactions within the molecule that contribute to its stability were investigated using natural bond orbital analysis, in order to research the molecule’s chemically active areas. Additionally, reactivity descriptors were determined. The moment of the electric dipole, initial static hyperpolarizability values, and polarizability have been studied for the title compound.